CloudBuild: Microsoft's Distributed and Caching Build Service - Esfahani, Hamed; Fietz, Jonas; Ke, Qi; Kolomiets, Alexei; Lan, Erica; Mavrinac, Erik; Schulte, Wolfram; Sanches, Newton; Kandula, Srikanth (SEIP, 2016)
Thousands of Microsoft engineers build and test hundreds of software products several times a day. It is essential that this continuous integration scales, guarantees short feedback cycles, and functions reliably with minimal human intervention. This paper describes CloudBuild, the build service infrastructure developed within Microsoft over the last few years. CloudBuild is responsible for all aspects of a continuous integration workflow, including builds, test and code analysis, as well as drops, package and symbol creation and storage. CloudBuild supports multiple build languages as long as they fulfill a coarse grained, file IO based contract. CloudBuild uses content based caching to run build-related tasks only when needed. Lastly, it builds on many machines in parallel. CloudBuild offers a reliable build service in the presence of unreliable components. It aims to rapidly onboard teams and hence has to support non-deterministic build tools and specification languages that under-declare dependencies. We will outline how we addressed these challenges and characterize the operations of CloudBuild. CloudBuild has on-boarded hundreds of codebases with only man-months of effort each. Some of these codebases are used by thousands of developers. The speed ups of build and test range from 1.3x to 10x, and service availability is 99%.